Experimental study on multiple tuned mass dampers to reduce seismic responses of a three storey building structure. - Chen, Genda (Earthquake engineering & structural dynamics.)
In this study, several mass dampers were designed and fabricated to suppress the seismic responses of a 1/4 scale three storey building structure. The dynamic properties of the dampers and structure were identified from free and forced vibration tests. The building structure with or without the dampers was, respectively, tested on a shake table under the while noise excitation, the scaled 1940 El Centro earthquake and the scaled 1952 Taft earthquake. The dampers were placed on the building floors using the sequential procedure developed by the authors in previous studies. Experimental results indicated that the multiple damper system is substantially superior to a single tuned mass damper in mitigating the floor accelerations even though the multiple dampers are sub optimal in terms of tuning frequency, damping and placement. These results validated the sequential procedure for placement of the multiple dampers. The structure was also analysed numerically based on the shake table excitation and the identified structure and damper parameters for all test cases. Numerical and experimental results are in good agreement, validating the dynamic properties identified.